Effects of the type of sugar and duration of fermentation on the quality of juice from banana (Musa balbisiana var. Cardaba) - Palmares, Ricardo III Jamora (2010.)
The purpose of this study is to compare the effects on quality of organic muscovado and molasses as added substrates to fermented banana juice at different duration periods.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana; Musa balbisiana var. Cardaba; Muscovado